2022
DOI: 10.1080/19491247.2022.2059845
|View full text |Cite
|
Sign up to set email alerts
|

Forced housing mobility and mental wellbeing: evidence from Australia

Abstract: This paper examines the links between forced housing mobility and the mental wellbeing of Australians in an era of heightened risks in both labour and housing markets. Specifically, we examine how the links between forced housing mobility and mental wellbeing vary according states of employment and housing tenure insecurity. Using the 2001-2018 Household, Income and Labour Dynamics in Australia Survey, we implement hybrid models across four mental wellbeing dimensions and uncover three key findings.First, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…However, this will only meet one-fifth of current unmet demand from public housing waitlist applicants. Other policy solutions will need to be added to the mix, including promoting business sector involvement in expanding social and affordable housing (SGS Economics and Planning 2022), incentivising landlords to offer longer-term secure leases to vulnerable households renting in the private rental sector (Wood et al 2017), and reforming tenancy laws that exacerbate precariousness in housing conditions for renters such as provisions for 'no grounds' evictions (Ong ViforJ et al 2022). More generally, systemwide increases to housing supply and relaxation of planning policies where they are restrictive can improve affordability and tenure security outcomes of vulnerable population groups.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…However, this will only meet one-fifth of current unmet demand from public housing waitlist applicants. Other policy solutions will need to be added to the mix, including promoting business sector involvement in expanding social and affordable housing (SGS Economics and Planning 2022), incentivising landlords to offer longer-term secure leases to vulnerable households renting in the private rental sector (Wood et al 2017), and reforming tenancy laws that exacerbate precariousness in housing conditions for renters such as provisions for 'no grounds' evictions (Ong ViforJ et al 2022). More generally, systemwide increases to housing supply and relaxation of planning policies where they are restrictive can improve affordability and tenure security outcomes of vulnerable population groups.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Eight out of 22 studies examined housing insecurity broadly, including not only renters but also other housing tenures such as homeowners, while analyzing renters separately in at least one analysis. Six studies identified their (sub-)samples as private renters (Baker, Lester, et al, 2020;Bentley et al, 2016;Mason et al, 2013;Reeves et al, 2016;ViforJ et al, 2022) and two as public renters (Baker, Lester, et al, 2020;Prentice & Scutella, 2020). Moreover, a number of studies examined specific population groups, such as low-income renter households (for more details see Table 1 and Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Specifically, Leifheit et al (2021) and Ali and Wehby (2022) observed a positive association between the eviction moratorium implemented in the U.S. in response to the COVID-19 pandemic and improved mental health of renters. Additionally, three studies found that experiencing forced mobility (C. Vásquez-Vera et al, 2022;ViforJ et al, 2022), or a higher frequency of moves (A. Li et al, 2022), respectively, were associated with a negative impact on the mental health of private renters in Australia and Spain.…”
Section: Housing Instability and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Our primary indicator of housing insecurity was self-reported housing payment problems, defined as living in a household that fell behind on rent or mortgage payments at any time in the past 12 months. As a secondary exposure we examined forced mobility, defined as having moved residence in the past 12 months either explicitly due to eviction or repossession, or any other move made by those who had reported difficulty paying rent or mortgage during the year 28 .…”
Section: Exposurementioning
confidence: 99%